Perancangan Sistem Informasi Pencatatan Data Maintenance Barang Sarana Prasarana Di Bagian Rumah Tangga Universitas Sebelas Maret Surakarta - kristanto, dwi (Politeknik Harapan Bangsa Surakarta, 2022)
The recording of data on maintenance of facilities and infrastructure at Sebelas Maret University, Surakarta (UNS) is still using a ledger and then copied to Microsoft Excel. The current management of maintenance data causes the making of infrastructure maintenance reports not on time. This has the effect of not being optimal in the care carried out by officers, so that infrastructure facilities are damaged quickly. Based on the description of the problem above, the researcher formulates the problem to be solved in this study,